Advanced schemes for underdense plasma photocathode wakefield accelerators: pathways towards ultrahigh brightness electron beams. (12th August 2019) - Manahan, G. G.; Habib, A. F.; Scherkl, P.; Ullmann, D.; Beaton, A.; Sutherland, A.; Kirwan, G.; Delinikolas, P.; Heinemann, T.; Altuijri, R.; Knetsch, A.; Karger, O.; et al.
Abstract : The 'Trojan Horse' underdense plasma photocathode scheme applied to electron beam-driven plasma wakefield acceleration has opened up a path which promises high controllability and tunability and to reach extremely good quality as regards emittance and five-dimensional beam brightness. This combination has the potential to improve the state-of-the-art in accelerator technology significantly. In this paper, we review the basic concepts of the Trojan Horse scheme and present advanced methods for tailoring both the injector laser pulses and the witness electron bunches and combine them with the Trojan Horse scheme. These new approaches will further enhance the beam qualities, such as transverse emittance and longitudinal energy spread, and may allow, for the first time, to produce ultrahigh six-dimensional brightness electron bunches, which is a necessary requirement for driving advanced radiation sources. This article is part of the Theo Murphy meeting issue 'Directions in particle beam-driven plasma wakefield acceleration'.